Automated Detection of Malaria-Associated Pseudoeosinophilia and Abnormal WBC Scattergram by the Sysmex XE-2100 Hematology Analyzer: A Clinical Study with 1,801 Patients and Real-Time Quantitative PCR Analysis in Vivax Malaria-Endemic Area - Yoo, Jong-Ha (The American Society of Tropical Medicine and Hygiene, 2010)
Recently, the XE-2100 hematology analyzer was investigated in a rather small patient group; pseudoeosinophilia or abnormal white blood cell (WBC) scattergrams reported by this instrument were considered as significantly valuable diagnostic parameters in detecting vivax malaria. This study was conducted not only to assess the usefulness of pseudoeosinophilia or abnormal WBC scattergram in vivax malaria-endemic areas with large patient groups (N = 1,801) but also to investigate the correlation of parasitemia and platelet count with pseudoeosinophilia and abnormal WBC scattergrams. Of the 1,801 analyzed patients, 413 (22.9%) were found to have malaria by Wright–Giemsa stained blood smears. Overall, either pseudoeosinophilia or abnormal WBC scattergram was detected in 191 of 413 malaria patients and 4 of 1,388 patients without malaria (sensitivity = 46.2%, specificity = 99.7%). We suggest that clinical hematology laboratories using the XE-2100 analyzer should be aware of such specific parameters, even with the absence of a clinical request.